TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK JUAL BELI BUAH RAMBUTAN YANG MASAK DI POHON DI DESA SEMANGA’ KECAMATAN SEJANGKUNG - Agustina (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The purpose of this research is to understand the practice of rambutan trading in Semanga Village, review the related aspects of Islamic law, and provide theoretical and practical insights to the community. In the literature review, Islamic law encompasses a set of norms derived from Allah SWT, and buying and selling is one form of contract regulated in Islam. This research methodology employs a qualitative approach, using data collection techniques such as observation, interviews, and documentation. Data analysis is conducted descriptively, with the researcher utilizing primary and secondary data sources to understand the practice of rambutan trading in Semanga Village. The data analysis techniques include data reduction, data presentation, and drawing conclusions. The research findings indicate that the practice of selling ripe rambutan on the tree is carried out to avoid losses due to the oversupply of harvests and continuously declining prices. Additionally, difficult access roads to the orchards and a lack of labor for harvesting the fruit are also challenges faced by farmers in Semanga Village